Design and implementation of fast data application based on information aggregation platform - Yanjie ZHAO (Dianxin kexue)
User behavior information contains great value.Telecom operators must collect and deal with this information to create new business growth point.Through the research of information collection and processing,the implementation scheme of fast data application was given.Services such as user care and information push were provided based on the behavior of position change and voice calls.The application was used in the new business field of China Telecom and achieved remarkable results.